2018
DOI: 10.1007/s11701-018-0790-9
|View full text |Cite|
|
Sign up to set email alerts
|

Patient perceptions of acute pain and activity disruption following inguinal hernia repair: a propensity-matched comparison of robotic-assisted, laparoscopic, and open approaches

Abstract: Few publications describe the potential benefit of robotic-assisted inguinal hernia repair on acute postoperative groin pain (APGP). This study compared patients’ perceptions of APGP, activity limitation, and overall satisfaction after robotic-assisted- (R), laparoscopic (L), or open (O) inguinal hernia repair (IHR). Random samples of patients from two web-based research panels and surgical practices were screened for patients who underwent IHR between October 28, 2015 and November 1, 2016. Qualified patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Inguinal hernias have been repaired through a variety of approaches with growing evidence comparing open, laparoscopic transabdominal preperitoneal, and totally extra‐peritoneal (TEP) approaches . The introduction of robotic surgery provides another emerging minimally invasive approach . A Cochrane review in 2003 showed superior outcomes for postoperative pain, numbness, haematoma formation and surgical site infection for TEP and transabdominal preperitoneal repair over open surgery .…”
Section: Introductionmentioning
confidence: 99%
“…Inguinal hernias have been repaired through a variety of approaches with growing evidence comparing open, laparoscopic transabdominal preperitoneal, and totally extra‐peritoneal (TEP) approaches . The introduction of robotic surgery provides another emerging minimally invasive approach . A Cochrane review in 2003 showed superior outcomes for postoperative pain, numbness, haematoma formation and surgical site infection for TEP and transabdominal preperitoneal repair over open surgery .…”
Section: Introductionmentioning
confidence: 99%
“…A non-statistically-significant trend was also reported toward a faster return-to-work in the RIHR group compared to the LIHR and open IHR groups (18.2 vs. 21.1 vs. 23.6 days, respectively), in a subgroup of patients. 6 As discussed earlier, previous studies have shown prolonged operative time and higher cost, while also having an improved recovery time and postoperative pain in robotic compared to laparoscopic IHR. 5 8 , 13 , 14 No study, with a significant population size, analyzed whether such outcomes change with a surgeon’s growing RIHR experience across the learning curve.…”
Section: Discussionmentioning
confidence: 81%
“… 5 In a propensity-matched analysis, patients without a prior IHR reported a significantly reduced postoperative inguinal pain score at one week in RIHR compared to LIHR and open IHR (3.8 vs. 4.9 vs. 5.5, respectively). 6 In the same study, a subgroup of patients who underwent RIHR reported significantly shorter time to stopping the use of prescribed pain medication postoperatively compared to LIHR and open IHR (9 vs. 12.6 vs. 11.2 days, respectively). A non-statistically-significant trend was also reported toward a faster return-to-work in the RIHR group compared to the LIHR and open IHR groups (18.2 vs. 21.1 vs. 23.6 days, respectively), in a subgroup of patients.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…With the development and popularization of minimally invasive techniques, laparoscopic techniques have been widely accepted due to the advantages of small trauma, rapid postoperative recovery and postoperative pain, and is gradually replacing traditional OS. 7 , 8 The robotic approach has been expected to be relevant to rectal cancer because the robotic interface is specifically suited for procedures in confined space, 9 while its safety and feasibility in the treatment of rectal cancer are uncertain. Our study aims to compare the 3 surgical approaches for rectal excision in a single institution.…”
Section: Discussionmentioning
confidence: 99%